Memórias conectadas: a tortura das ditaduras no cinema de ficção argentino, brasileiro e chileno - Ferreira, Alexandre Maccari (2024)
This study aims to analyze the construction of the connected cultural memory of torture in the civil-military dictatorships of Argentina, Brazil and Chile in fiction films released in the post-dictatorship periods. Narrative movies are a fertile field for the imagination and, when in contact with history, it provides an opportunity to reflect on certain themes that encompass societies. Among the approaches are the representations of violence promoted by States and the uses of torture as a mechanism of oppression and horror. The objects of analysis will be the sequences of physical torture, remembered or visualized, in fourteen films selected for the corpus. The methodological path is developed from the understanding of the socio-historical relationship of the selected films and the filmic analysis of the torture sequences. The study is organized into two theoretical chapters, one methodological and four analytical. In the first, the relations between cinema, public history and cultural memory and their connections are established. The second chapter covers the path of relations between cinema and violence in narrative films, investigating how the visual impact of violence and torture fueled the imagination of societies. Chapter three presents the definition of the corpus and the methodological approach. Chapters four, five and six understand the context of reflection of the Argentinean, Brazilian and Chilean filmographies, respectively, and analyze the torture sequences both as remembrance and as visuality. In Chapter seven investigates the connections and approximations motivated by cultural memory based on the visual and thematic elements expressed in the torture sequences. The main authors behind this study are Henry Rousso, Hans Ulrich Gumbrecht, Aleida Assmann, Joel Candau, Georges Didi-Huberman, Michael Pollak, Andreas Huyssen, Michael Rothenberg and Astrid Erll. The research problem is formulated as follows: how is the connected cultural memory of torture constructed in the films that represent the Argentinean, Brazilian and Chilean dictatorships in works of fiction released in the post-dictatorship period? The argumentative hypothesis with which we work is that torture sequences in films that are inspired by the history of dictatorships express a view that contextualizes national history as a type of cultural memory, but that, based on the recurrence of certain elements imagery, thematic, argumentative transcend this political border space to a memory that connects in the visual representations of the traumatic event and that reaches the heart of the discussion of human rights in the exposure of the abject connected by the uses of torture by States.